Peru 2020-2021: Household Income, Consumption, and Savings during the Pandemic - Francke, Pedro (2024)
Peru is among the countries hardest hit by the COVID-19 pandemic, experiencing significant losses in terms of lives and well-being. This study examines the income, expenditure, and savings patterns of Peruvian households amidst the pandemic, with a focus on rural / urban and formal / informal differences. Additionally, we analyze shifts in consumption, particularly regarding food and health expenditures. Utilizing data from the National Household Survey (ENAHO), we conducted a multi-period analysis at the quarterly level spanning 2019-2021, with the prepandemic quarter as the reference point. Our findings reveal substantial disparities between rural and urban areas, as well as within these segments based on the formal or informal employment status of household heads, regarding income, expenses, savings, and shifts in consumption patterns. While all segments experienced income reductions, rural households recovered swiftly but maintained reduced food consumption. Formal workers experienced less income loss and did not dissave, whereas urban informal workers were most affected in terms of income and food deprivation. Finally, we discuss how these findings can inform public policy discussions in Peru, particularly related to social protection.